2019
DOI: 10.1563/aaid-joi-d-18-00311
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Microbial Leakage of the Implant-Healing Abutment Interface in Four Connection Systems

Abstract: This study sought to assess microbial leakage through the implant-healing abutment interface in 4 dental implant connection systems. Ten implants of each of the 3i (double hexagon + flat to flat; group 1), IDI (internal hexagon + Morse taper; group 2), Swiss Plus (external bevel + internal octagon; group 3), and Tapered Screw-Vent (internal bevel + internal hexagon; group 4) systems were used in this in vitro, experimental study. Healing abutments were screwed to the implants with 10 Ncm torque. Implants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Pseudomonas aeruginosa has the ability to form biofilms and can be present in the bloodstream and periodontal infections. The use of those bacteria seems relevant for in vitro studies because these microorganisms have been found in periimplantitis lesions [ 17 , 27 , 28 , 32 , 33 ]. These bacteria were chosen over other known periodontal pathogens because they are easy to culture and because of their reduced size, their permeability through the microgap of the I-A interface, and their common residence in the peri-implant area [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa has the ability to form biofilms and can be present in the bloodstream and periodontal infections. The use of those bacteria seems relevant for in vitro studies because these microorganisms have been found in periimplantitis lesions [ 17 , 27 , 28 , 32 , 33 ]. These bacteria were chosen over other known periodontal pathogens because they are easy to culture and because of their reduced size, their permeability through the microgap of the I-A interface, and their common residence in the peri-implant area [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combined implant-abutment connections are characterized by the combination of geometric features that provide antirotational and prosthetic positioning properties [ 15 ]. Even when the implant and the abutment are correctly connected, microleakage produced by a microcap can be generated, allowing the passage of acids, enzymes, bacteria, and/or their metabolic products [ 3 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, perfect sealing at the IAC has not been provided by any implant system, and a complete hermetic seal is not yet achievable [ 24 ]. Ardakani et al [ 25 ] observed that microleakage through the IAC occurs in all implant systems, with special emphasis on torquing abutments to 20 N/cm to minimise microbial leakage. This statement is analogously supported by the results of this study in which a complete seal was not achieved either with different IAC types or with the use of sealing materials.…”
Section: Discussionmentioning
confidence: 99%
“…The micromotions at the IAI, which are known to result in ‘fretting wear’, 7 are complicated processes that are closely related to masticatory movements and act in accordance with the occlusion and temporomandibular joints 8 . Metal wear debris is an important product of fretting damage 9,10 . A mixture of this debris with microorganisms in saliva may enter the tissue surrounding the implant, which results in microleakages at the IAI 11 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Metal wear debris is an important product of fretting damage. 9,10 A mixture of this debris with microorganisms in saliva may enter the tissue surrounding the implant, which results in microleakages at the IAI. 11 Various studies have reported the roles of wear debris in peri-implantitis, [12][13][14] but the mechanisms underlying the metal wear debris generated by micromotions at the IAI have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%